SUBMERGED OR DESTROYED? RECONSTRUCTING AGRARIAN JUSTICE FOR COASTAL COMMUNITIES AFFECTED BY TIDAL FLOODING IN INDONESIA - Bunga Desyana Pratami; Imaro Sidqi (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
Tidal flooding increasingly threatens coastal land tenure in Indonesia by altering the physical condition, legal status, and socio-economic function of land. The central problem is the absence of clear legal parameters distinguishing temporarily submerged land from permanently destroyed land, despite the different consequences for land rights, certificates, registration records, and state responsibility. This study examines and reconstructs the legal protection of tidal-flood-affected land through Ronald Dworkin’s theory of justice as integrity. It employs doctrinal legal research using philosophical-hermeneutic, statutory, and conceptual approaches, focusing on the Basic Agrarian Law, Article 28H(4) of the 1945 Constitution of the Republic of Indonesia, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 17 of 2021. The study finds that the existing framework remains predominantly administrative, lacks firm criteria for transitional land conditions, and provides inadequate remedies for affected rights holders. Land should be classified as submerged where its boundaries remain identifiable, its legal relationship with the rights holder continues, and its physical or socio-economic function can still be restored. In such cases, land rights, certificates, and registration records must remain protected, supported by rehabilitation and administrative safeguards. Land may be classified as destroyed only where it has permanently lost its physical existence, identifiability, and socio-economic function. Although this classification may terminate land rights, it does not extinguish the state’s obligations toward former rights holders. Applying justice as integrity, this study reconstructs land-status determination by placing constitutional rights, equal concern and respect, socio-economic continuity, and proportional state responsibility at its core. Accordingly, the legal framework should require transparent procedures, meaningful participation, objections and remedies, fair compensation, appropriate relocation, and long-term socio-economic recovery. Indonesian agrarian law therefore requires reformulation to integrate administrative legal certainty with substantive justice and progressive climate-responsive protection for coastal communities affected by tidal flooding.